Analisis Kausalitas Pertumbuhan Ekonomi dan Pendapatan Asli Daerah Provinsi Bali Tahun 2000-2019 - Muhammad Ma'ruf; Yuni Prihadi Utomo (Universitas Batanghari Jambi, 2022)
Regional Original Income (PAD) and economic growth are important economic variables in a region. Economic growth in the long term can be defined as the process of increasing output per capita. This understanding contains three aspects, namely dynamic aspects, aspects of total output growth and population growth, and aspects of independence. The independence of a region is seen from the regional original income every year. This study aims to observe the causality pattern between economic growth and local revenue in Bali Province during the period 2000-2019 by using the Error Correction Model (ECM) causality test. The results of this study show that in Bali Province there is a two-way causal relationship between economic growth and local revenue. If economic growth increases it will have an impact on increasing regional original income, on the contrary if regional original income increases it will have an impact on increasing economic growth in the province of Bali.